(untitled) (Journal of Applied Oral Science, 2010)
Chlorhexidine gluconate (CHX) is recommended for a number of clinical procedures and it has been pointed out as a potential cavity cleanser to be applied before adhesive restoration of dental cavities. OBJECTIVE: As CHX may diffuse through the dentinal tubules to reach a monolayer of odontoblasts that underlies the dentin substrate, this study evaluated the cytotoxic effects of different concentrations of CHX on cultured odontoblast-like cells (MDPC-23). MATERIAL AND METHODS: Cells were cultured and exposed to CHX solutions at concentrations of 0.06%, 0.12%, 0.2%, 1% and 2%. Pure culture medium (α-MEM) and 3% hydrogen peroxide were used as negative and positive control, respectively. After exposing the cultured cells to the controls and CHX solutions for 60 s, 2 h or 60 s with a 24-h recovery period, cell metabolism (MTT assay) and total protein concentration were evaluated. Cell morphology was assessed under scanning electron microscopy. CHX had a dose-dependent toxic effect on the MDPC-23 cells. RESULTS: Statistically significant difference was observed when the cells were exposed to CHX in all periods (p